Genetic variation in metabolic phenotypes: study designs and applications - Suhre, Karsten; Gieger, Christian (Nature reviews. Genetics, 2012)
Key Points Technical advances in mass spectrometry and NMR spectroscopy enable genome-wide screens to be carried out for the association between genetic variants and hundreds of metabolic traits in a single experiment. Metabolite concentrations are direct readouts of biological processes and can play the part of intermediate phenotypes, providing functional links between genetic variance and disease end points in genome-wide association studies (GWASs). The first GWASs with metabolomics have already discovered many genetic variants in enzyme-, transporter- and other metabolism-related genes that induce major differences in the individual metabolic capabilities of the organism. Knowledge of the genetic basis of human metabolic individuality holds the key to understanding the interactions of genetic, environmental and lifestyle factors in the aetiology of complex disorders. We review emerging insights from recent GWASs with metabolomics and present design considerations for high-throughput metabolomics experiments with metabolic traits in epidemiological and clinical studies. Using ratios between metabolite concentrations can drastically increase the power of a metabolomics study and can provide functional information on the perturbed underlying biochemical pathways. Integration with other biochemical information, including data from other GWASs, can largely improve the value of the study. Current challenges and future directions include the addition of new sample types (other than urine and blood), extension of the metabolite panels, standardization between platforms and the development of adapted statistical and data analysis tools. Revealing genetic influences on metabolic phenotypes is important in further understanding the aetiology of many complex diseases. Here, the authors introduce study design considerations and applications for genome-wide association studies with metabolic traits. Many complex disorders are linked to metabolic phenotypes. Revealing genetic influences on metabolic phenotypes is key to a systems-wide understanding of their interactions with environmental and lifestyle factors in their aetiology, and we can now explore the genetics of large panels of metabolic traits by coupling genome-wide association studies and metabolomics. These genome-wide association studies are beginning to unravel the genetic contribution to human metabolic individuality and to demonstrate its relevance for biomedical and pharmaceutical research. Adopting the most appropriate study designs and analytical tools is paramount to further refining the genotype–phenotype map and eventually identifying the part played by genetic influences on metabolic phenotypes. We discuss such design considerations and applications in this Review.